Breastfeeding in the workplace: Other employees' attitudes towards services for lactating mothers - Labbok Miriam H; Abrahams Sheryl W; Suyes Kathryn (BMC, 2008)
Abstract Background Workplace accommodations for breastfeeding mothers are an important step towards achieving United States Healthy People 2010 goals for continued breastfeeding. However, evidence suggests that some employers wishing to accommodate lactating mothers fear negative reactions from other workers. Methods This study conducted in February 2007, used descriptive statistics and linear regression to assess attitudes towards workplace breastfeeding/milk expression among employees (n = 407) of a large U.S. corporation providing a wide variety of workplace accommodations for lactating mothers. Results Overall, attitudes about the impact of breastfeeding on the work environment were favorable. Previous exposure to a co-worker who breastfed or expressed milk during the work day was associated with a positive attitude towards workplace breastfeeding, even after controlling for respondents' gender, length of employment and personal breastfeeding history. Conclusion These preliminary findings suggest that lactation accommodations did not have negative repercussions for other employees, and that a corporate environment designed to enable and encourage continued breastfeeding does not endanger positive attitudes towards breastfeeding in other employees.